2008
DOI: 10.3390/molecules13092326
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole-based Potential Bi- and Tridentate Nitrogen Ligands: Synthesis, Characterization and Application in Asymmetric Catalysis

Abstract: Twelve new imidazole-based potential bi- and tridentate ligands were synthesized and characterized. Whereas in the first series the α-amino acid and imidazole moieties were linked by an amino bond, in the second series the tridentate ligands, containing two imidazole groups, were separated by an amide bond. The first series was obtained by the reductive amination of 2-phenylimidazole-4-carboxaldehyde with α‑amino acid esters. The tridentate ligands were prepared from 2‑phenylimidazole-4-carboxylic acid and chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The amino pyridine isomers L 2 , L 3 , and L 4 have conspicuously different effects on the polymerization rate. It is also observed that m-aminopyridine (L 3 ) or p-aminopyridine (L 4 ) is a more effective ligand than N-methylimidazole (L 1 ), which is perhaps the most widely employed aromatic ligand [15,16,17]. When L 4 is used, the fastest polymerization rate of 6.98 × 10 −4 mol/L·s is observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amino pyridine isomers L 2 , L 3 , and L 4 have conspicuously different effects on the polymerization rate. It is also observed that m-aminopyridine (L 3 ) or p-aminopyridine (L 4 ) is a more effective ligand than N-methylimidazole (L 1 ), which is perhaps the most widely employed aromatic ligand [15,16,17]. When L 4 is used, the fastest polymerization rate of 6.98 × 10 −4 mol/L·s is observed.…”
Section: Resultsmentioning
confidence: 99%
“…When L 4 was used, the lowest DPQ formation was obtained at 2.2%, and similar results were obtained under different experimental conditions. It is reported that the formation of DPQ is affected by various parameters, such as the polymerization temperature, types of solvent, polarity of reaction medium, and basicity of ligands, and its formation significantly increases as both solvent acidity and polymerization temperature increase [8,16,26,27,28]. DPQ production is the lowest with L 4 , which has the fastest reaction rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the pharmacologically relevant imidazole ring in the α,β -unsaturated-2-acyl imidazoles 2 is found in numerous natural products and ligands . It is also used as the precursor of N-heterocyclic carbenes, and the imidazole ring can easily be cleaved and functionalized (ester/amide surrogates) to different carbonyl analogues.…”
mentioning
confidence: 99%
“…Such compounds should possess higher coordination abilities towards transition metals, owing to the presence of nitrogen atoms. 4 Hence, in our previous studies, we focused on the synthesis of N-containing α-amino acid- [5][6][7][8][9][10][11] or tartaric acid-derived 12 compounds and their Cu 2+ complexes. The syntheses of target N-alkylated dicarbohydrazides were carried out in two ways.…”
Section: Introductionmentioning
confidence: 99%